The Effectiveness of Digital-Based Learning in Improving Beginning Reading Ability of First-Grade Elementary School Students - I Putu Suwekanaya; I Gede Suwindia; Kadek Aria Prima Dewi, PF (Lembaga Bale Literasi, 2026)
This study aims to analyze the effectiveness of digital-based learning in improving the beginning reading ability of first-grade students at SD Negeri 2 Sulahan, Susut District, Bangli Regency. The research employed a mixed method approach with an embedded concurrent design. The research subjects were 24 first-grade students in the second semester of the 2024/2025 academic year. Data collection was conducted through beginning reading tests, observation sheets, student response questionnaires, and documentation. The instruments had been tested for content validity (I-CVI = 0.88) and reliability (Cronbach's Alpha = 0.84). Quantitative data were analyzed using descriptive statistics and paired sample t-tests, while qualitative data were analyzed using data reduction, data presentation, and conclusion drawing. The results showed that digital-based learning was effective in improving students' beginning reading ability. The mean pretest score (58.2; SD=10.4) significantly increased to 81.5 (SD=8.7) in the posttest (t(23)=11.42; p<0.001; Cohen's d = 2.33 [very large effect]). Learning mastery increased from 33.3% to 87.5%. Student responses to digital-based learning were very positive (mean score 86.5%). This study concludes that digital-based learning has been proven effective and is recommended for improving the beginning reading ability of first-grade elementary school students.